1975
DOI: 10.1007/bf01070947
|View full text |Cite
|
Sign up to set email alerts
|

Antacid vs placebo in hospitalized gastric ulcer patients: A controlled therapeutic study

Abstract: Antacids are widely accepted as agents that promote healing and relieve pain of gastric ulcer. Well-controlled studies designed to test this belief are few. 28 patients with endoscopically proven gastric ulcer were treated for 3 weeks in hospital, 13 receiving a liquid placebo and 15 an antacid. All were followed by endoscopy to complete healing or until surgery was performed. 10 patients healed satisfactorily in the placebo group and 11 in the antacid group. All patients were free of pain during their hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For many years, the primary treatment option for ulcers was antacids. The effectiveness of antacids is unclear; some studies have shown some effectiveness (Lublin et al 1985), and others have not (Butler and Gersh 1975), but this treatment was all that was available, and, at least for some patients, antacids reduced pain. Refractory cases (then as now) were treated surgically.…”
Section: The Case Of Ulcer Diseasementioning
confidence: 99%
“…For many years, the primary treatment option for ulcers was antacids. The effectiveness of antacids is unclear; some studies have shown some effectiveness (Lublin et al 1985), and others have not (Butler and Gersh 1975), but this treatment was all that was available, and, at least for some patients, antacids reduced pain. Refractory cases (then as now) were treated surgically.…”
Section: The Case Of Ulcer Diseasementioning
confidence: 99%
“…Gaisberg et al (1975), carrying out a second endoscopy after four weeks of similar treatment, observed that 45 % of the ulcers were healed. Butler and Gersh (1975) found that three-quarters of gastric ulcers healed after three weeks' treatment in patients admitted to hospital; this ratio was similar in patients given antacids and in those given placebo. We decided to repeat endoscopy every week, and we chose two weeks as a standard treatment time, hoping that very effective control by m-PGE2 of the aggressive peptic factors might allow the crater to disappear before two weeks.…”
Section: Discussionmentioning
confidence: 89%